2012
DOI: 10.4995/wrs.2012.945
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intensive and extensive production systems on carcass quality in New Zealand White rabbits

Abstract: Forty New Zealand White rabbits weaned at 30 d were divided into 2 groups and reared under intensive or extensive production system until slaughter (91 d of age). In the extensive production system, rabbits were housed in free-standing cages on straw litter and fed farm-made feed ad libitum. Control rabbits were raised intensively in wire mesh slatted floor cages, indoors and on a commercial pellet ad libitum. Hot carcass weight was 16,6% lower (P<0.01) in extensive production. The difference of 1 point both i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
22
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 18 publications
9
22
2
1
Order By: Relevance
“…The contribution of cuts in rabbit carcass is determined by the adopted dissection lines, age and breed of rabbits, and, to a lesser extent, the dietary regime (Szkucik & Libelt 2006). The results obtained in our study were similar to those obtained in a study by Daszkiewicz et al (2012) and Gugołek et al (2015).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The contribution of cuts in rabbit carcass is determined by the adopted dissection lines, age and breed of rabbits, and, to a lesser extent, the dietary regime (Szkucik & Libelt 2006). The results obtained in our study were similar to those obtained in a study by Daszkiewicz et al (2012) and Gugołek et al (2015).…”
Section: Discussionsupporting
confidence: 82%
“…Similar results were achieved by Daszkiewicz et al (2012) in New Zealand White Rabbits, in an extensively fed group. In turn, as regards typical rabbits bred for meat, the slaughter yield calculated using this method is usually higher, and exceeds 50% (Zita et al 2007;Volek & Marounek 2009;Gugołek et al 2011;Strychalski, Juśkiewicz et al 2014;Gugołek et al 2015).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These results are in contrast with Pla (2008), who registered significantly higher hind part weight in organic rabbits than in the conventionally reared ones. On the other hand, Daszkiewicz et al (2012) observed significantly higher hind part weight in the intensive rather than in the extensive production system. Differences between the presented results and contrast data in literature might be affected by the type of housing and variable genotypes which were used in the studies.…”
Section: Resultsmentioning
confidence: 75%
“…W badaniach Daszkiewicza i wsp. [6] poziom białka w mięśniu longissimus dorsi królików NB wahał się od 22,18 do 22,78 %. Tabela 2.…”
Section: Wyniki I Dyskusjaunclassified